DIAMOND-BEARING KIMBERLITE FIELDS OF THE SIBERIAN CRATON AND THE EARLY PRECAMBRIAN GEODYNAMICS - Moralev V.M.; Glukhovsky M.Z. (My University, 2000)
Diamond-bearing kimberlite fields accounts for about 15% of the total number of kimberlite fields of the Siberian Craton (SC). Diamond-bearing kimberlites are invariably located above the high density rock masses identified by seismic surveys near the crust–mantle boundary despite the fact that almost all known fields were originated by Late Paleozoic–Early Mesozoic withinplate magmatism controlled locally by rift structures. In most of the cases, the isotopic age determinations show the Early Precambrian age of ultramafic and eclogitic xenoliths and inclusions in diamonds from kimberlites (from 2.0 up to 3.2–3.5 Ga). The high-density rock masses in the lower crust or upper mantle are interpreted as the Early Precambrian high-pressure diamond-bearing eclogitic and peridotitic residues after partial melting which are obviously the source of major quantity of kimberlite diamonds. The spatial distribution of fields seems to be tectonically controlled by radial and concentric fault zones of sialic nuclei, which are believed to be the most ancient preserved structural fragments of the continental crust. Hence, the “nucleus model” of the Early Precambrian geodynamics is considered to be the most plausible one for the understanding of the spatial distribution of the Siberian diamond-bearing kimberlite fields.
Keywords: Precambrian; Precambrian; Докембрий